2017
DOI: 10.1038/mp.2017.86
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2-regulated miRNAs control early human neurogenesis through differential effects on ERK and AKT signaling

Abstract: Rett Syndrome (RTT) is an X-linked, neurodevelopmental disorder caused primarily by mutations in the Methyl-CpG-binding protein 2 (MECP2) gene, which encodes a multifunctional epigenetic regulator with known links to a wide spectrum of neuropsychiatric disorders. While postnatal functions of MeCP2 have been thoroughly investigated, its role in prenatal brain development remains poorly understood. Given the well-established importance of miRNAs in neurogenesis, we employed isogenic human RTT patient-derived ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
182
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(188 citation statements)
references
References 76 publications
6
182
0
Order By: Relevance
“…However, these changes likely present well before clinical symptoms. For example, a recent hiPSC-based study has suggested that Rett may impact prenatal neurogenesis through microRNA-mediated changes in AKT and ERK activity 26 . Interestingly, while neuroanatomical changes in dendritic arborization and spine density have been reported in multiple Rett models 25,[27][28][29][30] , gross structural abnormalities are less prevalent.…”
Section: Rett Syndrome Fusion Organoids Exhibit Hypersynchronous Neurmentioning
confidence: 99%
“…However, these changes likely present well before clinical symptoms. For example, a recent hiPSC-based study has suggested that Rett may impact prenatal neurogenesis through microRNA-mediated changes in AKT and ERK activity 26 . Interestingly, while neuroanatomical changes in dendritic arborization and spine density have been reported in multiple Rett models 25,[27][28][29][30] , gross structural abnormalities are less prevalent.…”
Section: Rett Syndrome Fusion Organoids Exhibit Hypersynchronous Neurmentioning
confidence: 99%
“…S9). While PI3K/AKT (a hub in DE-ASD and XP-ASD networks) promotes proliferation and survival, many of the genes that are only hub in the XP-ASD network, including NRAS, ERK 1/2, and PTEN, can trigger differentiation of neural progenitor cells by mediating PI3K/AKT and its downstream pathways 3,44 .…”
Section: Signaling Pathways Are Central To the Leukocyte-based Networkmentioning
confidence: 99%
“…Organoids. Organoids were grown according to the protocol by Lancaster et al 59 , with the addition of dual SMAD inhibition between d6 and d9 to increase neural differentiation as previously described 60 . Organoids were grown from iPSC cells (System Biosciences, #SC101A-1).…”
Section: Discussionmentioning
confidence: 99%